Organizational misbehavior: roles of perception of injustice, negative-positive affectivity and ethical ideology - Akın, Zeynep (My University, 2006)
Bu araştırmanın ana hedefi, örgüte zararlı davranışların (organizational misbehavior) ortaya çıkmasında, adaletsizlik algısının rolünü incelemektir. Bu çalışmada, adaletin üç boyutu: paylaşım, işlemsel ve etkileşim adaletlerinin olduğu ve olmadığı durumlarda, çalışanların ne tip zararlı davranışlar içerisine girecekleri araştırılmıştır. Ayrıca, çalışanların negatif-pozitif duygu durumunun, adaletsizlik algıları ile ve sahip oldukları ahlaki ideolojilerin ise örgüte zararlı davranışları ile olan ilişkilerine de bakılmıştır. Adalet boyutlarının etkisinin ayarlanışı, adalet ortamları farklı olan sekiz senaryo ile yapılmıştır. Her denek senaryoların sadece bir tanesini okumuş, senaryoda hikâye edilen şahsın, belirtilen zararlı davranışları yapma sıklığını derecelendirmiştir. Ayrıca deneklerin, adaletsizlik algılarını, negatif-pozitif duygu durumlarını ve ahlaki ideolojilerini ölçen testler de verilmiştir. Elde edilen sonuçlara göre, kişilerin adaletsizlik algısı arttıkça, örgüte zararlı davranışları da artmaktadır. Adaletsizlik algısı ile örgüte zararlı davranışlar arasında doğrusal bir ilişki bulunmaktadır. Buna karşılık, adaletsizlik algısı arttıkça, örgütsel vatandaşlık davranışı azalmaktadır. Fakat yüksek idealizm devreye girdiğinde, bu ilişkiler yön değiştirmektedir. Yüksek idealizme sahip kişilerin adaletsizlik algıları ile örgüte zararlı davranışları arasında ters yönlü, vatandaşlık davranışları ile doğrusal bir ilişki bulunmuştur. Adaletsizlik algısı artsa dahi, algının yüksek idealizm ile etkileşime girmesi sonucu, örgüte zararlı davranışlar düşmektedir. Ayrıca, negatif-pozitif duygu durumunun, adaletsizlik algısı üzerinde manidar bir etkisi olmadığı bulunmuştur.

The central task of this study is to examine the role of injustice perception in the emergence of organizational misbehavior. In this research, the types of organizational misbehaviors have been studied in two conditions in which the three dimensions of justice (distributive, procedural and interactional justice) were present and in which they were absent. In addition, the relationship between negative-positive affectivity and injustice perception as well as the relationship between ethical ideology and organizational misbehaviors were also examined. The effect of injustice dimensions was arranged through eight scenarios in which the justice conditions differed. Each subject has only read one of the scenarios and rated the frequency of organizational misbehaviors of the actor in that scenario. In addition, tests that measured the subjects’ injustice perception, negative-positive affectivity and ethical ideology have also been used. According to the results, as the injustice perception increases, so do people’s organizational misbehaviors. There is a linear relationship between injustice perception and organizational misbehaviors. As opposed to this finding, as the injustice perception increases, the behavior of organizational citizenship decreases. However, these relationships change direction when high idealism interferes. It has been found that the injustice perception of people who have high idealism has a reverse relationship with their organizational misbehaviors, while it has a linear relationship with their organizational citizenship behaviors. As a result of high idealism’s interaction with the injustice perception, organizational misbehaviors decrease even if the injustice perception increases. Furthermore, it has been found that the negative-positive affectivity has no significant effect on the injustice perception.
Keywords: Adalet_Örgütsel Davranış; Örgüte Zararlı Davranışlar_işletmeler